2018
DOI: 10.1038/s41467-018-05969-w
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the mechanisms of membrane protein export by virulence-associated bacterial secretion systems

Abstract: Many bacteria export effector proteins fulfilling their function in membranes of a eukaryotic host. These effector membrane proteins appear to contain signals for two incompatible bacterial secretion pathways in the same protein: a specific export signal, as well as transmembrane segments that one would expect to mediate targeting to the bacterial inner membrane. Here, we show that the transmembrane segments of effector proteins of type III and type IV secretion systems indeed integrate in the membrane as requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 51 publications
(81 reference statements)
1
53
1
Order By: Relevance
“…We also compared the average Gibbs free energy (Δ G app ) values that are associated with the insertion of TMDs from the translocon to the IM and that varied with the positions, lengths, and amphiphilicities of residues in the TMDs ( 50 ). Because the identified single-spanning proteins of the two classes belong mostly to the targeted class and the single-spanning proteins had lower Δ G app values than multispanning proteins ( 51 ), we further divided each class into single-spanning and multispanning classes to rectify this comparison. The TMD1s of the targeted class proteins had a Δ G app value similar to that of the untargeted class proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also compared the average Gibbs free energy (Δ G app ) values that are associated with the insertion of TMDs from the translocon to the IM and that varied with the positions, lengths, and amphiphilicities of residues in the TMDs ( 50 ). Because the identified single-spanning proteins of the two classes belong mostly to the targeted class and the single-spanning proteins had lower Δ G app values than multispanning proteins ( 51 ), we further divided each class into single-spanning and multispanning classes to rectify this comparison. The TMD1s of the targeted class proteins had a Δ G app value similar to that of the untargeted class proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 2015 ; Krampen et al. 2018 ). Furthermore, binding of the Salmonella chaperone SicA was found to prevent degradation of both SipB and SipC by cytosolic proteases (Tucker and Galan 2000 ).…”
Section: Substrate Targeting and Secretionmentioning
confidence: 99%
“…Thus, a TMD that meets the hydrophobicity requirements for functioning both at the C terminus of an IMP and internally in a type II IMP may use different mechanisms to achieve efficient membrane insertion. Interestingly, a recent study describes a subset of effector proteins that are secreted via the type III and type IV secretion systems and yet have predicted TMDs of moderate hydrophobicity (37). It was shown that the predicted TMDs can indeed insert in the inner membrane when they are grafted into a polytopic IMP, suggesting a similar context dependency of TMD functioning.…”
Section: Discussionmentioning
confidence: 99%